From Thermodynamics to Information: Landauer’s Limit and Negentropy Principle Applied to Magnetic Skyrmions - Zivieri, Roberto (Frontiers in Physics, 2022)
Magnetic skyrmions are topologically protected objects that can be manipulated and employed as information carriers. This is accomplished basing either on their ground-state properties or on their thermodynamic properties. Landauer’s principle establishes an irreversible conversion from information to physics. In this perspective article, the inverse mechanism is proposed for magnetic topological defects forming in magnetic nanostructures that are regarded as closed thermodynamic systems confirming Szilard’s and Brillouin’s hypotheses. This mechanism consists of the creation of bits of information using a thermodynamic source having the form of negentropy. In this perspective article it is proved for small swirling topological defects such as magnetic skyrmions: a) the Landauer’s principle expressed in terms of negentropy and b) the generalized second principle of thermodynamics based on Brillouin’s negentropy principle of information. The thermodynamic entropy is converted into information entropy at the expenses of negentropy, a “negative entropy” corresponding to the loss of thermodynamic entropy by the magnetic skyrmion itself. A recently proposed practical device enables the verification of point a) and b) and allows a full understanding of the interchange between thermodynamics and information and vice versa showing, in perspective, the considerable advantages offered by this type of storing and coding information.